Rudarsko industrijska regija Zasavje, skozi različne oblike (ne)pravičnosti - Žnidarič, Davorin (Teorija in praksa, 2025)
In the article, the author deals with the issue of the crisis facing the industrial mining region of Zasavje and what has caused its problems over time. T hrough an analysis of justice, the author constructively and especially critically examines the consequences of the situation in the region that has brought the once economically prosperous region into the grip of environmental and social stagnation. Different segments of injustice are illuminated via specific actions of national and local decision-makers and politicians and politicians in the region. Constructive critical analysis leads the author to find causes that, alongside environmental degradation due to the impacts of long-term intensive and non-ecological industrial activity in certain geographical and weather conditions, has seen the region suffer environmental, social and social injustice. In the concluding part, the author focuses on social systems and the reasons explaining the lack of critical public attention to how industry in the region has functioned and solutions aimed at its use by society, the environment and nature by way of a transformed rule of rights and decision-making structures. At the same time, such solutions can reduce irregularities in the region.
Keywords: constructive critical analysis; environmental justice; konstruktivno kritična analiza; mining and energy region; neenakost; non-environmental and non-ecological practices; okoljska pravičnost; rudarsko energetska regija; rule of law; škodljiva in neekološka ravnanja; vladavina prava; Zasavje